Nirgundi Oil: A Potential Therapeutic Agent For Managing Diabetic Wound. - Sudesh, Gupta; Anjana, Sharma (International Research Journal of Ayurveda & Yoga, 2021)
Background-Today’s increasing fast lifestyle poverty and imbalanced ecosystem, problem of wound contamination and infection increasing day by day. Person hardly get time to look after his personal health. Method- The present study was designed to study role of Nirgundi taila (Vitex negundo) in Pramehaja vrana i.e diabetic wound. For this study 30 patients were randomly selected and the efficacy of the drugs were put into trial on these patients. Result-On completion of trial the statistical analysis concludes the percentage of relief in parameters i.e Pain - 81.79%,discharge -93.01%, burning sensation- 90.53%, granulation tissue- 86.69%, itching-95.51%, numbness -100%. Conclusion- The research work finally conclude that Nirgundi taila (Vitex negundo) have a potent wound healing property in diabetic wound management and also showed an improved rate of wound contraction and reduction in healing time in patients treated with Nirgundi taila application.